Optimisation of Thin Film Copper Iodide as a p-type Transparent Thermoelectric Material - Gomes, Diogo Manuel Lúcio Veloso Cunha (2018)
Alternative energy sources are being explored to reduce on fossil fuels and pollutant emissions. Green energy sources such as thermoelectric materials converters require little maintenance. Life-time testing has shown the capability of thermoelectric devices to exceed 100,000 h of steady-state operation. On the other hand, they are used for applications with high energetic relevance that include temperature control of scientific instruments to household air-cooling systems. The current trend for development of transparent, flexible and large area electronics, creates other challenges in terms of applications and development of thermoelectric materials. Some of the transparent oxide materials and conductors of n-type present adequate properties for application in thermoelectric devices. In the case of cooling processes, these need n-type and p-type elements. For the current scarcity of existing p-type elements, copper iodide is one of those which better fulfills all requirements: transparent and p-type electrical conductive, an abundant and environment friendly material. In this dissertation, CuI thin films (ca. 100-300nm) were produced through methods of copper iodination via vapour or solid, and deposited via resistive thermal evaporation of copper iodide, obtaining the γ-CuI phase in all cases. The thickness of Cu films was varied and the influence of iodination times studied, in vapour and solid methods. In samples prepared via thermal evaporation, a thorough analysis of the thickness effect on electrical properties was studied. The obtained results have shown to be possible to obtain films with transmittances over 75% in the range of visible light, with a band gap of 3.05 eV, Seebeck values above 200 μV/K, electrical conductivity above 500 Ω-1m-1, holes mobility of around 3x1019 cm-3 in films with 400 nm thicknesses obtained via solid and vapour iodination. Besides this study, different geometries of thermoelectric modules formed by films of CuI and AZO were also tested and so demonstrating the potential of copper iodide as a transparent p-type semiconductor in thermoelectric devices.